2008
DOI: 10.3928/00989134-20080301-02
|View full text |Cite
|
Sign up to set email alerts
|

CNA Empowerment: Effects on Job Performance and Work Attitudes

Abstract: In this analysis, the effects of empowerment were examined among a sample of certified nursing assistants (CNAs) representing a wide range of empowerment levels. On the basis of survey responses from 298 CNAs and 136 nurses in five nursing homes where CNA-empowered work teams had been implemented and five nursing homes with more traditional management approaches, the results indicated that CNA empowerment had a variety of effects. CNAs with high empowerment and the nurses who worked with them tended to report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…The results indicate that participants would view an employer positively for providing the training, and that they perceived that the training would be of benefit to their care of residents and to their job satisfaction and performance. These findings support research that suggests that training to improve job skills can increase job satisfaction and job commitment, and it may be an important element of the formula to decrease worker turnover (Cready, Yeatts, Gosdin, & Potts, 2008; Sengupta, Harris-Kojetin, & Ejaz, 2010; Yeatts et al, 2010). Crandall, White, Schuldheis, and Talerico (2007) studied the adoption of culture change by nine LTC facilities.…”
Section: Discussionsupporting
confidence: 83%
“…The results indicate that participants would view an employer positively for providing the training, and that they perceived that the training would be of benefit to their care of residents and to their job satisfaction and performance. These findings support research that suggests that training to improve job skills can increase job satisfaction and job commitment, and it may be an important element of the formula to decrease worker turnover (Cready, Yeatts, Gosdin, & Potts, 2008; Sengupta, Harris-Kojetin, & Ejaz, 2010; Yeatts et al, 2010). Crandall, White, Schuldheis, and Talerico (2007) studied the adoption of culture change by nine LTC facilities.…”
Section: Discussionsupporting
confidence: 83%
“…Forty-two studies were included in the review. The majority ( n = 29) of studies used a cross-sectional survey design [ 9 , 10 , 33 , 46 – 48 , 52 54 , 56 58 , 60 – 62 , 64 , 66 – 71 , 73 – 75 , 77 – 79 , 93 ]. Of these, 1 study used mixed methods (survey plus qualitative data) [ 78 ], 1 study used a randomized controlled trial [ 59 ], and 7 studies used observational before-and-after quasi-experimental (pre/posttest) design [ 49 , 51 , 55 , 65 , 72 , 76 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the 44 quality assessments, 5 (11%) studies were rated strong [ 9 , 78 , 81 , 84 , 85 ], 6 (14%) high moderate [ 53 , 56 , 66 68 , 73 ], 15 (34%) low moderate [ 10 , 52 , 57 , 58 , 61 , 64 , 65 , 69 , 71 , 72 , 75 , 76 , 78 , 83 , 93 ], and 18 (41%) weak [ 33 , 46 – 49 , 51 , 54 , 55 , 59 , 60 , 62 , 70 , 74 , 77 , 79 , 80 , 82 ]. Differences in quality assessment arose mainly from sample representativeness, treatment of missing data, and appropriateness of statistical test(s) used.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review found that individual factors influencing care aides’ job satisfaction were empowerment and autonomy, while organizational factors included facility resources and workload [ 26 ]. Cready et al reported survey findings from care aides and nurses from facilities where care aide empowered teams had been implemented and from facilities with more traditional management approaches, and found that feelings of high empowerment among care aides were associated with higher assessments of their job performance and job satisfaction [ 27 ]. Indeed, strategies to empower the care aide workforce may draw on their high levels of job efficacy, that is, a sense of their work’s worth [ 12 , 28 ].…”
Section: Discussionmentioning
confidence: 99%